2016
DOI: 10.1016/j.bbrc.2016.04.151
|View full text |Cite
|
Sign up to set email alerts
|

3-Bromopyruvate and sodium citrate induce apoptosis in human gastric cancer cell line MGC-803 by inhibiting glycolysis and promoting mitochondria-regulated apoptosis pathway

Abstract: Cancer cells are mainly dependent on glycolysis to generate adenosine triphosphate (ATP) and intermediates required for cell growth and proliferation. Thus, inhibition of glycolysis might be of therapeutic value in antitumor treatment. Our previously studies had found that both 3-bromopyruvate (BP) and sodium citrate (SCT) can inhibit tumor growth and proliferation in vitro and in vivo. However, the mechanism involved in the BP and SCT mediated antitumor activity is not entirely clear. In this work, it is demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Compared with the results of Xingyu Guo, Xiaodong Zhang et al (2016), who researched the effects of citrate on MGC-803 stomach cancer cell lines in 48 hours, the IC 50 value was 10.08 ± 0.87 mM 11 . The IC 50 of citrate on HepG2 line in our study was found to be 1.25-fold higher than that of stomach cancer cells 11 . To confirm the effects of citrate on HepG2 proliferation through activation of apoptosis, we evaluated the phenotype of apoptotic cells via the expression of Annexin-V.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Compared with the results of Xingyu Guo, Xiaodong Zhang et al (2016), who researched the effects of citrate on MGC-803 stomach cancer cell lines in 48 hours, the IC 50 value was 10.08 ± 0.87 mM 11 . The IC 50 of citrate on HepG2 line in our study was found to be 1.25-fold higher than that of stomach cancer cells 11 . To confirm the effects of citrate on HepG2 proliferation through activation of apoptosis, we evaluated the phenotype of apoptotic cells via the expression of Annexin-V.…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, HepG2 cells were treated with citrate at various concentrations-from 60 mM to 1.5 mM in 48 h. The IC 50 result of citrate was 12.650 ± 0.115 mM. Compared with the results of Xingyu Guo, Xiaodong Zhang et al (2016), who researched the effects of citrate on MGC-803 stomach cancer cell lines in 48 hours, the IC 50 value was 10.08 ± 0.87 mM 11 . The IC 50 of citrate on HepG2 line in our study was found to be 1.25-fold higher than that of stomach cancer cells 11 .…”
Section: Discussionmentioning
confidence: 84%
“…Another issue that needs to be addressed is the pathway underlying the 3BP-induced cell death, apoptosis or necrosis. Some studies provided evidences that 3BP inhibits cancer cells growth while promoting apoptosis pathways such as down-regulation of anti-apoptosis proteins Bcl-2 and survivin, up-regulation of proapoptosis protein Bax, activation of caspase-3, as well as leakage of cytochrome c to cytoplasm [23,24]. On the other hand, in consistent with these studies, other reports provided evidence that 3BP induces mainly necrosis rather than apoptosis, showing that 3BP induced generation of ROS species, loss of outer mitochondrial membrane permeability, and rapid ATP depletion leading to necrotic cell death [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, Survivin is introduced as a multi-functional protein and reducing the expression of survivin is closely related to tumor death and drug inhibition. In fact, many studies have shown that patients with high survival mRNA expressions have a short life (WANG et al, 2016;GUO et al, 2016;HU et al, 2017). Therefore, amygdalin that used in this study via decreasing of survivin mRNA expressions leads to apoptosis and cell death in cancer cell line like MCF-7, and this naturally occurring chemical compound is useful for prevention and inhibition of the spread of cancer.…”
Section: Verification Of Cdna Synthesismentioning
confidence: 93%